The Influence Of Tiktok Social Media On The Musicality Of Al-Ihsan Tanjung Lago Banyuasin High School Students Pandemi Covid-19 - Arining Wibowo; Riyu Wansyah (Cinematology: Journal Anthology of Film and Television Studies, 2023)
Tiktok is a social media application and also a music video platform, users can imagine and freely express ideas as creatively as possible in the form of short videos. The purpose of this study is to measure and find out how the influence or effectiveness, impact and benefits of TikTok social media on the musicality of students of Al-Ihsan Tanjung Lago High School, Banyuasin Regency, South Sumatra. This study used a sample of students of Al-Ihsan Tanjung Lago High School. Purposive sampling was applied and distributed questionnaires to respondents to be filled out voluntarily. The results of this study, based on data disseminated to respondents through questionnaires, have been processed and show that there is an influence between Tiktok Social Media on the Musicality of Al-Ihsan Tanjung Lago Banyuasin High School Students.